Marketing-quality interface: An empirical analysis of FMCG customers - Sumreen Khalil (Cogent Business & Management, 2021)
This research intends to study the interface of key concepts of Marketing and Quality in relation to Fast Moving Consumer Goods (FMCG) Customers. Marketing variables i.e. product, price, place and promotion are exogenous variables, quality perception is the endogenous variable whereas Word of Mouth (WOM) is the mediating variable for this study. For achieving the objectives of this research and test the developed hypotheses, a quantitative research strategy has been followed. In order to collect data, on the basis of literature, a questionnaire has been developed by the researcher. This research has significance in terms of its contribution both theoretically and practically as it has developed an instrument for measuring FMCG customers' quality perception. Moreover, a model has also been developed which is statistically validated. Data have been collected from 466 customers from Lahore using Stratified Random Sampling Technique. AMOS has been used for developing structural model and testing of hypotheses. Findings of the research conclude that all marketing variables i.e. price, place and promotion except product has an interface with perceived quality of FMCG customers and these relationships are mediated through WOM.
Keywords: 650; Interface; marketing variables; product; price; place; promotion; quality perception; fast-moving consumer goods; word of mouth